IDENTIFIKASI JENIS KEPITING DI PERAIRAN MOLAS, KECAMATAN BUNAKEN, KOTA MANADO (Identification Of Crab Species in Molas Waters, Bunaken District, Manado City) - Reygina B.S Roring; Erly Y. Kaligis; Robert A. Bara; Nickson J. Kawung; Winda M. Mingkid (Sam Ratulangi University, 2023)
Crustaceans are an important part of the bentic fauna and one of the groups is infra theorderbrachyura. Brachyura crabs cover about 700 genera and about 5000 to 10000 species. Thepurpose of this study is first to identfy the types of crabs, secondly to calculate abundance, thirdly tofind out the environmetal conditions of the surrounding waters both pH, temperature, salinity occupiedby the types of crabs in Molas waters, Bunaken District, Manado Cit. Identification technique based onthe color and shape of the carapace. The data collection location consists of 2 different places (station)which are 150 m between stations. To compelte the data in the field, supporting water quality data wasalso collected such as: temperature, pH, and salinity at each station. Identification results in Molaswaters, Bunaken District, Manado City found 7 types of crabs with the number recorded namely,Austruca annulipes 155 individuals, followed by Ocypode sp 55 individuals, Ocyopde palidula 53individuals, Leptograpsus variegatus 30 individuals, Gelasimus vocans 20 individuals, Aratus pisonii 15individuals and Portunus pelagicus 10 individuals. Based on the analysis of abudance data with thehighest value, namely Crab Austruca annulipes that is1,55 ind/m2. The quality parameters in Molaswaters are temperature 29-30 oC, Salinity ppt 29-30 ppt, pH 6-8.Keywords: Molas, Crabs, Abudance ABSTRAKKrustasea adalah bagian penting dari fauna bentik dan salah satu kelompok adalah infra ordobrachyura. Kepiting brachyura mencakup sekitar 700 genera dan sekitar 5000 hingga 10.000 spesies.Tujuan dari penelitian ini adalah yang pertama mengidentifikasi jenis-jenis kepiting, kedua yaitumenghitung kelimpahan, ketiga yaitu mengetahui keadaan lingkungan perairan sekitar baik pH, suhu,salinitas yang di tempati oleh jenis-jenis kepiting di perairan Molas, Kecamatan Bunaken, Kota Manado.Penelitian ini menggunakan metode jelajah. Teknik identifikasi berdasarkan warna serta bentukkarapas. Lokasi pengambilan data terdiri 2 tempat (stasion) berbeda yang berjarak 150 m antar stasion.ntuk melengkapi data di lapangan diambil juga data pendukung kualitas air, seperti: suhu, pH, dansalinitas pada masing-masing stasiun. Hasil identifikasi di Perairan Molas, Kecamatan Bunaken, KotaManado ditemukan 7 jenis kepiting dengan jumlah yang terdata yaitu, Austruca Annulipes yaitu 155individu, kemudian diikuti jenis kepiting Ocypode sp yaitu 55 individu, Ocypode palidula yaitu 53individu, Leptograpsus variegatus yaitu 30 individu, Gelasimus vocans yaitu 20 individu, Aratus pisonii15 individu dan Portunus pelagicus 10 individu. Berdasarkan analisis data kelimpahan dengan nilaitertinggi yakni Kepiting Austruca annulipes yaitu 1,55 ind/m2. Parameter kualitas di perairan Molas yaitusuhu 29-30 oC, salinitas 29-30 ppt, pH 6-8.Kata kunci: Molas, Kepiting, Kelimpahan